Proteomic study of gamma-oryzanol preventive effect on a diet-induced non-alcoholic fatty liver disease model - Siqueira, Juliana Silva; Garcia, Jéssica Leite; Ferron, Artur Junio Togneri; Moreto, Fernando; Sormani, Luís Eduardo; Costa, Mariane Róvero; Palacio, Thiago Luiz Novaga; Nai, Gisele Alborghetti; Aldini, Giancarlo; Ferron, Fabiane Valentini Francisqueti; Camacho, Camila Renata Correa; D'Amato, Alfonsina (Elsevier, 2024)
Nonalcoholic fatty liver disease (NAFLD) is the most common liver disease associated with obesity and diabetes prevalence. The use of natural compounds has become an attractive approach to prevent NAFLD and its progression. Gamma-oryzanol (Orz) is a natural compound whose beneficial effects on chronic metabolic diseases have been reported. Therefore, we aimed to investigate the preventive effect of Orz on the hepatic proteome in a diet induced NAFLD model. Wistar rats were randomly distributed into three experimental groups (n=6/group) according to the diet received for 30 weeks: Control group, high sugar-fat (HSF) group, and HSF+Orz group. The isolated Orz was added to the chow at the dose of 0.5% (w/w). We evaluated the nutritional profile, characterized the presence of steatosis through histological analysis, triglyceride content in liver tissue and hepatic inflammation. Next, we performed label-free quantitative proteomics of hepatic tissue. Network analysis was performed to describe involved protein pathways. NAFLD induction was characterized by the presence of hepatic steatosis. Orz prevented lipid accumulation. The compound prevented alterations of the hepatic proteome, highlighted by the modulation of lipid metabolism, inflammation, oxidative stress, xenobiotic metabolism, and the sirtuin signaling pathway. It was possible to identify key altered pathways of NAFLD pathophysiology modulated by Orz which may provide insights into NAFLD treatment targets.